2020
DOI: 10.1177/0887403420913621
|View full text |Cite
|
Sign up to set email alerts
|

Examining Vocational Rehabilitation Services Provided to Incarcerated Persons With Disabilities

Abstract: In the U.S. prison system, incarcerated persons with a disability represent a largely marginalized population with limited or inadequate provision of services in prison. In general, once released, ex-offenders face a number of challenges when they reenter society ranging from access to housing, employment, health care, and substance use services. These challenges are generally exacerbated for incarcerated persons with a disability. Overall, there is a dearth of research on rates of vocational services utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Across these descriptive and correlational studies, we found varying sample sizes. Some studies relied on large-scale epidemiological surveys-e.g., the Survey of Prison Inmates (Maruschak, Bronson, and Alper, 2021;Bixby, Bevan, and Boen, 2022), National Inmate Survey (Bronson, Maruschak, and Berzofsky, 2015), or National Survey of Drug Use and Health (Winkelman et al, 2020)-or administrative datasets (e.g., data from the Rehabilitation Services Administration; Baloch and Jennings, 2021), and these studies included sample sizes of 15,000 individuals or more. But other studies relied on smaller samples, including those that involved primary data collection.…”
Section: Topics and Methodological Approaches Within The Quantitative...mentioning
confidence: 99%
See 1 more Smart Citation
“…Across these descriptive and correlational studies, we found varying sample sizes. Some studies relied on large-scale epidemiological surveys-e.g., the Survey of Prison Inmates (Maruschak, Bronson, and Alper, 2021;Bixby, Bevan, and Boen, 2022), National Inmate Survey (Bronson, Maruschak, and Berzofsky, 2015), or National Survey of Drug Use and Health (Winkelman et al, 2020)-or administrative datasets (e.g., data from the Rehabilitation Services Administration; Baloch and Jennings, 2021), and these studies included sample sizes of 15,000 individuals or more. But other studies relied on smaller samples, including those that involved primary data collection.…”
Section: Topics and Methodological Approaches Within The Quantitative...mentioning
confidence: 99%
“…For this reason, it was more challenging to identify a consistent set of themes within this subset of the literature. Criminal legal topics included studies relating to efforts to apply for Supplemental Security Income/Social Security Disability Income (SSI/SSDI) following release from incarceration (Sajadi, 2021), participation in vocational rehabilitation (Baloch and Jennings, 2021), courtroom accessibility (Riehl, 2008), and provision of accommodations in correctional settings (Parry, 2009;Seevers, 2016).…”
Section: Other Physical Disabilitiesmentioning
confidence: 99%